The complex role of microbial metabolic activity in fossilization. (14th October 2021) - Janssen, Kathrin; Mähler, Bastian; Rust, Jes; Bierbaum, Gabriele; McCoy, Victoria E.
ABSTRACT: Bacteria play an important role in the fossilization of soft tissues; their metabolic activities drive the destruction of the tissues and also strongly influence mineralization. Some environmental conditions, such as anoxia, cold temperatures, and high salinity, are considered widely to promote fossilization by modulating bacterial activity. However, bacteria are extremely diverse, and have developed metabolic adaptations to a wide range of stressful conditions. Therefore, the influence of the environment on bacterial activity, and of their metabolic activity on fossilization, is complex. A number of examples illustrate that simple, general assumptions about the role of bacteria in soft tissue fossilization cannot explain all preservational pathways: ( i ) experimental results show that soft tissues of cnidaria decay less in oxic than anoxic conditions, and in the fossil record are found more commonly in fossil sites deposited under oxic conditions rather than anoxic environments; ( ii ) siderite concretions, which often entomb soft tissue fossils, precipitate due to a complex mixture of sulfate‐ and iron reduction by some bacterial species, running counter to original theories that iron reduction is the primary driver of siderite concretion growth; ( iii ) arthropod brains, now widely accepted to be preserved in many Cambrian fossil sites, are one of the first structures to decay in taphonomic experiments, indicating that their fossilization processes are complex and influenced by bacterial activity. In order to expand our understanding of the complex process of bacterially driven soft tissue fossilization, more research needs to be done, on fossils themselves and in taphonomic experiments, to determine how the complex variation in microbial metabolic activity influences decay and mineralization.